2016
DOI: 10.1117/1.nph.3.3.031415
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for high-yield acquisition of functional near-infrared spectroscopy data from alert, upright infants

Abstract: Abstract. Functional near-infrared spectroscopy (fNIRS) research to date has tended to publish group-averaged rather than individual infant data due to normative basic research goals. Acquisition of individual infant time courses holds interest, however, both for cognitive science and particularly for clinical applications. Infants are more difficult to study than adults as they cannot be instructed to remain still. In addressing this, upright infants pose several associated complications for the researcher. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Different acquisition paradigms for the study of the prefrontal cortex via f-NIRS have been proposed in the literature. [38][39][40][41][42][43][44][45] The participants to the learning path collected from the literature different procedures for the stimulation (auditory, visual, visuospatial-auditory, visuospatial-visual, auditory-visual and visuospatial). After long discussions about the benefits and limitations of the mainly used acquisition procedures, they decided to investigate the effects of memory tasks, since it has been shown that they elicit hemodynamic responses in the brain.…”
Section: F-nirs Based Oi Analysis Of the Mental Workloadmentioning
confidence: 99%
“…Different acquisition paradigms for the study of the prefrontal cortex via f-NIRS have been proposed in the literature. [38][39][40][41][42][43][44][45] The participants to the learning path collected from the literature different procedures for the stimulation (auditory, visual, visuospatial-auditory, visuospatial-visual, auditory-visual and visuospatial). After long discussions about the benefits and limitations of the mainly used acquisition procedures, they decided to investigate the effects of memory tasks, since it has been shown that they elicit hemodynamic responses in the brain.…”
Section: F-nirs Based Oi Analysis Of the Mental Workloadmentioning
confidence: 99%
“…b) Rapid and large (> 0.1 au) signal changes produced by motion artifacts. rate amplitude and that they typically take at least 2 s from start to peak (Goodwin et al, 2016;Arichi et al, 2012), motion artifacts were defined as any change in signal passing an amplitude threshold of at least 0.1 OD units (i.e. five times the heart rate amplitude) within a 1 s interval (Figure 2b).…”
Section: Motion Correction Proceduresmentioning
confidence: 99%
“…Translating these general strategies into specific implementations that perform well (i.e. remove artifacts while retaining hemodynamic responses) across participants and samples has nonetheless turned out to be a difficult challenge (Brigadoi et al, 2014;Cooper et al, 2012;Goodwin et al, 2016;Behrendt, Firk, Nelson & Perdue, 2018;Di Lorenzo et al, 2019;Hu et al, 2015;Barker, Aarabi & Huppert, 2013;Reyes, Bohache, Wijeakumar & Spencer, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the cortical source of EEG is difficult to definitively determine, as the electrical activity measured by EEG propagates and sums across the scalp, physical constraints on light propagation and detection through underlying tissue reduce source localization estimates in NIRS data to a few centimeters around a given data channel's (light source-detector pair) scalp placement (Cui et al, 2011;Luck, 2005;Minagawa-Kawai, 2008). The increase in use and application of fNIRS has been accompanied by advances in hardware, software, and head probes to meet data collection and data processing challenges (Aasted et al, 2015;Gervain et al, 2011;Goodwin et al, 2016;Huppert et al, 2009;Lloyd-Fox et al, 2010;Santosa et al, 2018;Ye et al, 2009;Yücel et al, 2017;Saikia et al, 2019;Zimmermann et al, 2019). However, parallel advances in data analysis are needed for fNIRS to become and remain a premier method for studying brain function in infants (Gervain et al, 2011;Powell et al, 2018, Gemignani & Gervain, 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%